Development of the armenian “Big five” questionnaire - Serobyan, Astghik (Bulletin of Yerevan University E: Philosophy, Psychology, 2021)
The article presents the main phases of the "Big Five" questionnaire development, the results of reliability and validity. The whole process was carried out in two consecutive research stages. Initially, the “Big Five” questionnaire consist 150 questions, which measured 5 main factors and 30 subfactors. However, after processes that include two phases questionnaire development, the number of questions was reduced to 125. As a result, the number of subfactors became 25, and for each main factor there were 5 subfactors instead of 6. Afterwards we get a reliable and valid questionnaire in armenian that could be used to measure personality traits, as well as for using in all areas where it is necessary to identify the personality traits, for example, human resources management, education, etc.